The study of cotton (Gossypium hirsutum L.) accessions in Krasnodar Region - S. V. Grigoryev; T. V. Yakusheva (Труды по прикладной ботанике, генетике и селекции)
Background. Cotton production, processing and trade are essential part of the world economy. The acreage under cultivated cotton over the world has expanded during the past five years, while total production of cotton fiber has increased almost twice. Cotton is the most demanded natural fiber in Russia: the share of pure cotton in Russian commercial textile trade is up to 54%. Effective use of Russia's diverse climate conditions to solve priority tasks of the domestic industry and agriculture has high innovative importance, considering that the share of imported cotton in the country's total textile inputs used by its light industry is 40%. Therefore, it is urgent and important enough to evaluate the effect of soil and climate conditions in the south of Russia on cotton yield and fiber quality.Materials and methods. In 2016, a research was accomplished to evaluate the accessions of Gossypium hirsutum L. listed in the introduction catalogue in the steppe areas of Prikubanskaya Plain, Krasnodar Region (Kuban Experiment Station of VIR, Gulkevichi District), according to VIR's guidelines. The most important features of cotton fiber were estimated in the context of the trends existing on the world market (HVI testing).Results and conclusions. Accessions that produced 75 -100% of mature plants after 120 days of vegetation were described. Fiber yield of the studied white fiber accessions was not high. With some exceptions, accessions yielding naturally colored fiber had lower productivity than white fiber ones. The accession i-604984 exceeded the reference in fiber productivity, boll weight, and fiber harvest. The results of HVI tests showed that the evaluated accessions yielded fiber of good quality (4-5th type of the O'zDSt604-2001 standard, Uzbekistan). Fiber of the accessions i-604971 and i-604975 had the best strength. The fibers of all accessions demonstrated high or very high degree of uniformity in length. All white fiber accessions demonstrated normal micronaire values, quite acceptable for textile industry. Micronaire indicators of colored cotton accessions were only slightly lower than those of white fiber ones in maturity and fineness, but these differences were not significant when compared with the references.